PENGARUH REKRUTMEN TERHADAP KINERJA KARYAWAN PADA PT BANK RIAU KEPRI CABANG TELUK KUANTAN - Repis Kayanti; Seno Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research was conducted at the Bank riau kepri the study aims to determine the effect of recruitment to employee performance. Recruitment as an independent variable (X), while the performance of the employee as the dependent variable (Y).Samples are 28 respondents, all employees of a Bank riau kepri data obtained from the questionnaire and further processed to then be tested with statistics through SPSS program. Results of calculation of the coefficient of determination is 0,609. That is to say, the recruitmen affects the performance of employees amounted to 60,9%.Keywords : Recruitment, Employee Performance, bank riau kepri